Kritik Nalar Filsafat Ketuhanan Versi Islam Dan Barat (Kajian Pemikiran Ibn Rusyd Dan Alfred North Whitehead) - suhandi, suhandi; Azis, Abdul; Musofa, Ade (Universitas Islam Negeri Raden Intan Lampung, 2023)
This article is a study of divine philosophy that more specifically discusses the concept of divinity by Ibn Rushd and Alfred North Whitehead. The method used consists of two stages: concept formation (tashawur) and logical reasoning (tashdiq). Ibn Rushd's epistemological thinking contains certain implications and consequences. First, Ibn Ruyd's concept of two sources of knowledge can encourage a meeting between religion and science, as well as religion and philosophy, but on the other hand it can also give birth to materialistic, secular and even atheistic thoughts, at least the doctrine of